The sunk cost fallacy in venture capital staging: Decision-making dynamics for follow-on investment rounds - Hogrebe, Fabian; Lutz, Eva (Journal of Corporate Finance, 2024)
The decision to participate in a follow-on investment round is fundamental for venture capitalists, as it determines the extent of financial and non-financial resources they will provide to the portfolio company going forward. In this context, we analyze the effect of sunk costs, i.e., the invested capital and monitoring efforts expended, on the likelihood of subsequent funding. Based on a dataset of 30,602 investment decisions about US-based portfolio companies from 2009 to 2019, we find that both the amount of capital previously invested and the intensity of monitoring significantly increase the probability of continued investment, underscoring the sunk cost fallacy's role in venture capital. Additionally, we investigate the moderating effects of fund maturity, represented by dry powder and fund age, on these relationships. The results highlight the intricate balance between investment biases and fund-level considerations in venture capital decisions, contributing to the behavioral finance literature.